Dystrophin is expressed in smooth muscle and afferent nerve fibers in the rat urinary bladder - Lionarons, Judith M. (Muscle Nerve, 2019)
INTRODUCTION: With increasing life expectancy, comorbidities become overt in Duchenne muscular dystrophy (DMD). Although micturition problems are common, bladder function is poorly understood in DMD. We studied dystrophin expression and multiple isoform involvement in the bladder during maturation to gain insights into their roles in micturition. METHODS: Dystrophin distribution was evaluated in rat bladders by immunohistochemical colocalization with smooth muscle, interstitial, urothelial, and neuronal markers. Protein levels of Dp140, Dp71, and smooth muscle were quantitated by Western blotting of neonatal to adult rat bladders. RESULTS: Dystrophin colocalized with smooth muscle cells and afferent nerve fibers. Dp71 was expressed two‐ to threefold higher compared with Dp140, independently of age. Age‐related muscle mass changes did not influence isoform expression levels. DISCUSSION: Dystrophin is expressed in smooth muscle cells and afferent nerve fibers in the urinary bladder, which underscores that micturition problems in DMD may have not solely a myogenic but also a neurogenic origin. Muscle Nerve 60: 202–210, 2019